2015
DOI: 10.1002/asjc.1140
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Thf‐Fxlms Algorithm For Active Noise Control With Loudspeaker Nonlinearity

Abstract: Adaptive algorithms are prevalently applied in the design of nonlinear active noise control (ANC) systems. The most important nonlinearity in ANC is the saturation effect produced by the electro‐acoustical sensors and transducers. The dominant saturation nonlinearity is in the transducers, which can be represented by a Wiener model. An effective solution to mitigate such nonlinear distortion is to employ the Nonlinear Filtered‐X Least Mean Square (NLFXLMS) algorithm. The controller compensates the nonlinearity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Even though the values of the estimated secondary path may not necessarily converge to their true values, the controller will compensate this effect by adjusting its gain during adaptation. This gain swapping effect has been observed in the previous works .…”
Section: Proposed Thf‐nlfxlms Algorithmsupporting
confidence: 84%
See 4 more Smart Citations
“…Even though the values of the estimated secondary path may not necessarily converge to their true values, the controller will compensate this effect by adjusting its gain during adaptation. This gain swapping effect has been observed in the previous works .…”
Section: Proposed Thf‐nlfxlms Algorithmsupporting
confidence: 84%
“…It was shown that the degree of nonlinearity in can be related to the degree of nonlinearity in by : α=2η2 β=12η2 These relations are applicable to the Hammerstein and Wiener THF‐NLFXLMS algorithms, and are also applicable to the Wiener‐Hammerstein THF‐NLFXLMS algorithm.…”
Section: Wiener‐hammerstein Nlfxlms Contol Algorithmmentioning
confidence: 92%
See 3 more Smart Citations